Investigation of the Antibacterial Effects of Some Plant Extracts on Propionibacterium acnes - Serpi, Muhammed; Ozdemir, Zafer Omer; Salman, Yasemin (KAHRAMANMARAS SUTCU IMAM UNIV, 2012)
Acne vulgaris (Acne) is a disease of the sebaceous glands, and especially affects the facial region. In this study, Matricaria chamomilla (chamomile), Alchemilla vulgaris (lady's mantle), Lavandula angustufolia (lavender), Melissa officinalis (melissa), Fumaria officinalis (fumeterre) and Punica granatum (pomegranate) bark extract's antibacterial activity were determined against 6 different strains of Propionibacterium acnes. Plant extracts concentrations in the 2 mg/ml and 5 mg/ml used in our study were observed antibacterial activity against clinical P. acnes strains, which used in this study, and 0.5 mg/ml concentration of the plant extract showed no antibacterial activity. 5 mg/ml concentration is prevent reproduction (antibacterial activity) 100%, 2 mg/ml plant extracts concentration prevent reproduction 100%, excluding extract of Matricaria chamomilla and bark extract of Punica granatum. As a result of this study, a new effective herbal based preparations, which will developed, may have the potential both to become an alternative and to support classical acne treatment, is identified.
Keywords: Acne vulgaris; Antibacterial activity; Plant Extract; Propionibacterium acnes; Agriculture